Sistem Pendukung Keputusan Penentuan Kelayakan Pembangunan Crane Menggunakan Metode Analytic Hierarchy Process - Technique For Order Preference By Similarity To Ideal Solution (AHP-TOPSIS) [Studi Kasus PT. MHE DEMAG, Surabaya] - Fendra Gunawan; Imam Cholissodin; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In the construction of the project in the transfer of objects that can not be moved by humans, a transporter is needed, one of which is a crane. Problems with PT. MHE-Demag, Surabaya in determining the initial feasibility of crane construction is the effectiveness and efficiency of time. The solution to the problem requires an application that can process data into a decision support system that is useful to provide the right decision in determining the feasibility of crane construction. The AHP-TOPSIS method was chosen because the method was able to select the best alternative from the alternative determination of the existing crane. The test used is by performing a pairwise comparison matrix to obtain priority weight for each criterion, the right hierarchy, and the ideal amount of data. The results obtained with the combination of values ​​in pairwise comparison matrix and application of Level 1 hierarchy match obtained the value of λmax = 7.53058 CI = 0.08843, CR = 0.067 resulted in a matching level of 92%. The ideal amount of data in this study is to obtain high accuracy values ​​using 10 to 20 data.